Transforming South African Public- Sector Supply Chain Using Public-Private Partnership Business Acumen - Mathu, Ken (The journal of contemporary issues in business and government, 2019)
This study focused on the South African public sector supply chain (PSSC), and the role of public-private partners hips (PPP) projects in executing public service delivery. The poor public service delivery caused by perpetual protests and blockades of public facilities by angry communit ies prompted this research. The study looks at the possibility of applying PPPs business acumen, or commercial initiative to the PSSC to enhance public service delivery. The PSSC and some of the PPP projects established after the country’s democratic dispensation in 1994 were explored in pursuit of a solution to the service delivery dilemma. The theory of collaboration and integration formed the basis of the study. A qualitative research methodology was pursued, and senior manage rs from the South African Treasury and PPPs were interviewed. The study established that the business acumen or commercial initiative applied by PPP projects through supply chain collaboration and integrat ion enhanced public sector delivery, and, thus, PPPs are a more suitable model than the prevailing PSSC processes.